Didactic conditions for formation of skills of conscious construction of image in beginning artists - O.I. Furman (Academy of Cognitive and Natural Sciences, 2009)
In the article the didactic terms of farming are examined conscious the prosess of construction of image the students of KHGF on the initial stage of study of picture.